ADAPTIVE BIOPHILIC SPACE BASED ON ARDUINO UNO FOR VISUAL COMFORT AND STRESS-RESPONSIVE VENTILATION - Bobby Alexander Riady; Ridwan Sanjaya (JoDA Journal of Digital Architecture, 2026)
This study presents a prototype of an adaptive biophilic room using an Arduino Uno platform, designed to respond to users’ physiological stress conditions and ambient light intensity. The system employs a heartbeat sensor placed on the fingertip as a simplified indicator of stress level and a Light Dependent Resistor (LDR) to detect variations in room lighting. These inputs control actuators consisting of a servo motor that simulates window opening as a representation of ventilation and an LED operated using Pulse Width Modulation (PWM) to represent adaptive lighting. The research method includes electronic circuit design, development of adaptive control logic, and experimental simulations under various heart rate (BPM) and lighting conditions. The results indicate that when BPM exceeds a predefined threshold (90 BPM), the system automatically activates a relaxation mode by opening the simulated window and dimming the light. LED intensity is also adjusted according to ambient light conditions to maintain visual comfort within low to moderate illumination levels. Integrated testing demonstrates that the system operates stably and responsively during continuous use. This prototype highlights the potential of low-cost microcontrollers to support adaptive biophilic environments that can respond to human physiological conditions through real-time control of lighting and ventilation.